2015
DOI: 10.1039/c4ta06556e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LnF3 on reversible and cyclic hydrogen sorption behaviors in NaBH4: electronic nature of Ln versus crystallographic factors

Abstract: The suitable electronegativity and stable electron configuration of Ln3+, with the unique crystal structure of Ln–B phases contribute to the improvement in reversible hydrogen storage properties of NaBH4–LnF3 composites. The 3NaBH4–GdF3 composite shows the best cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Christian et al [165] the LiBH 4 -TiF 3 system and confirmed that the TiB 2 and LiF formed during dehydrogenation, which affected the reaction enthalpy. Chong et al [161] introduced several lanthanide elements fluorides into NaBH 4 , and observed that the 3NaBH 4 -GaF 3 composites displayed a fast kinetics and remained high cycling stability even after 51 cycles. Richter et al [177] reported that milling with LiBF 4 could significantly decrease the decomposition temperature of LiBH 4 , but only diborane gas was released during this process.…”
Section: Adding Dopantsmentioning
confidence: 99%
“…Christian et al [165] the LiBH 4 -TiF 3 system and confirmed that the TiB 2 and LiF formed during dehydrogenation, which affected the reaction enthalpy. Chong et al [161] introduced several lanthanide elements fluorides into NaBH 4 , and observed that the 3NaBH 4 -GaF 3 composites displayed a fast kinetics and remained high cycling stability even after 51 cycles. Richter et al [177] reported that milling with LiBF 4 could significantly decrease the decomposition temperature of LiBH 4 , but only diborane gas was released during this process.…”
Section: Adding Dopantsmentioning
confidence: 99%
“…It suggested that CeB 6 kept stable and had no positive effect on rehydrogenation, which was different from what was observed in the 3NaBH 4 /CeF 3 composite. 41 According to the work of Gennari et al, 48 we concluded that the side reaction occurred in the 3LiBH 4 /graphene-10 wt% CeF 3 composite can be described as:…”
Section: Mechanisms Of De/re-hydrogenationmentioning
confidence: 99%
“…4(b) and (c), ball-milled samples of the 3LiBH 4 /graphene and 3LiBH 4 /graphene-10 wt% CeF 3 composites revealed the characteristic absorption peaks of B-H stretching band at 2361, 2313(2327), 2276 cm À1 and B-H bending band at 1095 and 1237 cm À1 , quite close to the pure LiBH 4 (2361, 2307, 2276, 1095 and 1237 cm À1 ). The slight shi might be attributed to the charge-transfer from LiBH 4 to graphene and CeF 3 , 33,41 or caused by the FTIR technique itself. Fig.…”
Section: Mechanisms Of De/re-hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, hydrogen sorption reversibility was achieved in 3NaBH 4 /LnF 3 systems with good thermodynamic and kinetic properties. 34 Considering that scandium lies in the III B column of the periodic table as the lanthanide elements, we attempt to prepare a new hydrogen storage system, 3NaBH 4 /ScF 3 , through ball milling method. Our previous investigations on NaBH 4 -MF 3 (M ¼ metal) systems proved that the molar ratio of 3 : 1 was the best one, i.e.…”
Section: Introductionmentioning
confidence: 99%